1987
DOI: 10.1111/j.1471-4159.1987.tb05633.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Comparison of the Photoaffinity‐Labeled Benzodiazepine Receptor Subunits

Abstract: The late evolutionary appearance of the benzodiazepine receptor (BZR) allows an experimental approach for evaluation of the qualitative development of its subunits. Photoaffinity labeling of brain membranes with [3H]flunitrazepam followed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and fluorography offers a suitable method for tracing the qualitative evolution of the BZR. A systematic comparison of the subunit patterns in fishes, amphibians, reptiles, birds, and mammals revealed that the subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 19 publications
(23 reference statements)
2
25
1
Order By: Relevance
“…As previously found [24], [25], [38], the presence of putative GABA α-, β- and ρ-like receptor subunits in the genome of C. intestinalis support that this ancestral duplication most likely occurred before the divergence of urochordates. These results suggest that benzodiazepine sensitivity evolved early, in marked contrast to previous proposals [39], [40]. In line with our finding, recent electrophysiological data suggest that invertebrates (e.g., Hydra vulgaris ) are responsive to benzodiazepine modulation and this response is similar to the response to GABA [41].…”
Section: Discussionsupporting
confidence: 88%
“…As previously found [24], [25], [38], the presence of putative GABA α-, β- and ρ-like receptor subunits in the genome of C. intestinalis support that this ancestral duplication most likely occurred before the divergence of urochordates. These results suggest that benzodiazepine sensitivity evolved early, in marked contrast to previous proposals [39], [40]. In line with our finding, recent electrophysiological data suggest that invertebrates (e.g., Hydra vulgaris ) are responsive to benzodiazepine modulation and this response is similar to the response to GABA [41].…”
Section: Discussionsupporting
confidence: 88%
“…A comparison among mammalian, amphibian, and fish brains demonstrated that a common protein with molecular mass of -5 1 kDa is intensely photoaffinity labeled by [3H]Flu in most species studied of mammals, birds, amphibians, and reptiles, except fish, where a 55-kDa protein is labeled instead (Hebebrand et al, 1986(Hebebrand et al, , 1987. Insects show two bands at 46 and 59 kDa photolabeled by [3H]Flu; their relationship to mammalian GABAA receptors is unclear (Robinson et al, 1986).…”
Section: Phylogeny and Ontogeny Of Bz Receptorsmentioning
confidence: 99%
“…This ligand labels a 50 to 52 kDa polypeptide band in mammalian brain (Mohler et al, 1980), although additional minor species of higher molecular mass are detectable in some brain regions (Sieghart et al, 1983;Fuchs and Sieghart, 1989;Bureau and Olsen, 1990). A phylogenetic study revealed that a major labeled polypeptide of the same molecular mass (51 kDa) was present in brain from tetrapods, amphibians, and the primitive lungfish (Hebebrand et al, 1986(Hebebrand et al, , 1987. Additional labeled polypeptides were detected in several species of reptiles, birds, and mammals, suggesting an isoreceptor complex arising by gene duplication and subsequent divergence (Hebebrand et al, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photoaffinity labeling experiments with [3H]flunitrazepam ([3H]FNZ) have indicated that the asubunit carries the benzodiazepine (BZ) binding site (Mohler et al, 1980). Photoaffinity labeling of crude synaptic membranes with [3H]FNZ followed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and fluorography revealed regional as well as species variations of the M, values of the BZ binding proteins (Sieghart and Karobath, 1980;Hebebrand et al, 1987). Species variation and regional heterogeneity of the M, values of the BZ binding proteins persisted after deglycosylation with endoglycosidase F (Endo F) .…”
mentioning
confidence: 99%